2000
DOI: 10.1139/x00-014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of millipedes on litter decomposition, N mineralization, and microbial communities in a coastal forest in British Columbia, Canada

Abstract: Laboratory experiments were conducted with the millipede Harpaphe haydeniana haydeniana Wood (Polydesmida: Xystodesmidae) to determine (i) its litter feeding preferences, (ii) rates of leaf litter consumption, (iii) feeding effects on available nitrogen, and (iv) functional microbial diversity. The millipede exhibited a preference for Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) and, to a lesser extent, Sitka spruce (Picea sitchensis (Bong.) Carrière) litter compared with western hemlock (Tsuga heterophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
2
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 27 publications
1
65
2
3
Order By: Relevance
“…Soil fauna have been found to increase decomposition, mineralization and respiration in forest soils (Anderson et al, 1985;Setälä andHuhta, 1990, 1991). Macrofauna such as millipedes fragment leaf litter thereby increasing the surface area available for microbial attack and accelerating its break down (Anderson and Bignell, 1980;Cárcamo et al, 2000). Mesofauna (mites, collembolans and enchytraeid potworms) and microfauna (protozoa and nematodes) feed on bacteria and fungal mycelia (Klironomos and Kendrick, 1995) preventing fungistasis and disperse fungal inocula (Visser, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Soil fauna have been found to increase decomposition, mineralization and respiration in forest soils (Anderson et al, 1985;Setälä andHuhta, 1990, 1991). Macrofauna such as millipedes fragment leaf litter thereby increasing the surface area available for microbial attack and accelerating its break down (Anderson and Bignell, 1980;Cárcamo et al, 2000). Mesofauna (mites, collembolans and enchytraeid potworms) and microfauna (protozoa and nematodes) feed on bacteria and fungal mycelia (Klironomos and Kendrick, 1995) preventing fungistasis and disperse fungal inocula (Visser, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Los organismos del primer orden, los llamados milpiés, se alimentan de hojas secas o descompuestas de muchas plantas inclusive de la familia Meliaceae, (Cárcamo et al 2000), la cual presenta algunos géneros con actividad antimalárica (Chinchilla et al 1996). Además varias especies de este orden secretan sustancias de defensa (Cárcamo et al 2000) cuya composición química podría ser la causante del efecto indicado.…”
Section: Discussionunclassified
“…Los organismos del primer orden, los llamados milpiés, se alimentan de hojas secas o descompuestas de muchas plantas inclusive de la familia Meliaceae, (Cárcamo et al 2000), la cual presenta algunos géneros con actividad antimalárica (Chinchilla et al 1996). Además varias especies de este orden secretan sustancias de defensa (Cárcamo et al 2000) cuya composición química podría ser la causante del efecto indicado. En cuanto a las especies del orden Opiliones, se ha encontrado que estos organismos se alimentan de varias especies de artrópodos dentro de los que se incluye larvas y adultos de lepidópteros, coleópteros y hemíp-teros fítófagos (Lawrence 1981, Santos et al 2002, por lo cual estos podrían ser la fuente indirecta de productos activos provenientes de plantas.…”
Section: Discussionunclassified
“…The presence of millipedes has also been found to greatly increase the release of litter nutrients into the soil, especially calcium and nitrates (Pramanik et al, 2001). Millipedes are selective about what leaves they eat (Lyford, 1943;Kheirallah, 1979;Cárcamo et al, 2000). The chemical composition of leaf litter, especially the lignin and nitrogen content, can greatly affect soil fauna populations, although this effect is not clear for millipedes (Tian et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of leaf litter, especially the lignin and nitrogen content, can greatly affect soil fauna populations, although this effect is not clear for millipedes (Tian et al, 1993). Van der Drift (1975) estimated that in temperate areas millipedes are responsible for ingesting 5-10 percent of the annual leaf litter fall and Cárcamo et al (2000) estimated that a single species of millipede consumed 36 percent of the annual leaf litter in a British Columbian Cedar-Hemlock forest. Tropical studies have also found a large influence of millipedes on decomposition (Tian et al, 1995).…”
Section: Introductionmentioning
confidence: 99%